Legal and water management policy during climate warming in Poland - Marszelewski, Michał; Piasecki, Adam (Bulletin of Geography. Socio-economic Series, 2021)
The article discusses some of the effects of global warming on rivers, lakes and underground water in Poland. It documents serious difficulties in river shipping and energy, as well as the exposing of areas previously occupied by lakes as a result water levels lowering. It is pointed out that the rapid increase in intensive irrigation of agricultural areas is causing excessive exploitation of underground water. The analysis takes into account the relevant data. The presentation of the effects of global warming is expanded upon with the legal provisions applicable in these situations. In the absence of climate change law, these are general regulations that face a number of difficulties in application. The detailing of areas of law and hydrology leads to the conclusion that Poland lacks a coherent policy on climate warming.